Method for calculating a water surface profile at the watershed scale with little observed data based on ASTER GDEM: a case study in the Naoli River, northeast China - Tian, Lin; Wei, Yinying; Wang, Sheng; Zhang, Guorong; Zhao, Chuangjia; Huang, Xin; Huang, Weiyu (Frontiers in Environmental Engineering, 2024)
The calculation of a river water surface profile is a very important problem in the field of hydraulic engineering. With the development of research on surface and groundwater coupled simulation, the river water surface profile has become an indispensable boundary condition for simulating the inter-relationship between surface water and groundwater. River channel large-section data are the basic prerequisites for building most hydrodynamic models, and obtaining field data can consume considerable effort and material resources. We extracted river sections using ArcGIS based on the ASTER GDEM data and interpolated the corresponding water levels of different guarantee flow rates in Baoqing and Caizuizi stations. We analyzed the variation of upstream water levels under different Manning coefficients n, and the bed resistance of the Naoli River was determined to be 0.025. In order to ensure the rationality of the model and the reliability of the operation results, three indexes (non-scouring velocity, the shear stress of the riverbed, and the water surface slope) were used to analyze and test the rationality of the simulation results. Ultimately, the calculation of the water surface profile from the Baoqing hydrologic station to the Caizuizi hydrologic station in the Naoli River was achieved using the MIKE 11 hydrodynamics model under the guarantee flow rates of 20%, 50%, 75%, and 95%. Calculating the water surface profile can provide hydrological boundary conditions for surface and groundwater conversion and the combined simulation. Furthermore, the present study can provide a feasible method for calculating a river water surface profile in areas that lack measured section data.